(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
The B. bassiana is a fungus of manyarthropods, including more than 200 species of insects and acaridae. When spores of the fungus come into contact with the body of an insect host, they germinate, enter the body, and grow inside, eventually killing the insect. Two local strains, including B. bassiana-G07, which was isolated from grasshopper Oedaleusasiaticus, died on natural infection, and B. bassiana-G10, which was isolated from grasshopper Caliptomus abbreviates, died of soil borne infection, were detected and it was identified as species B. bassiana by PCR. SCAR primers OPB9 F/R677 and OPA15 F/R441 was specific to of B. bassiana. The highest infection rate by B. bassiana-G07and mortality was observed in variants of both concentrations 2.1 x 108 conidia/ml, 2.1 x 109 conidia/ml; where mortality reached 86.3-100%. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 96-100